Long-term outcomes of third-line therapy with tyrosine kinase inhibitors in chronic phase chronic myeloid leukemia: A real-life experience - Chitanava, Tamara; Matvienko, Iuliia; Shuvaev, Vasily; Voloshin, Sergey; Martynkevich, Irina; Vlasova, Yulia; Efremova, Elizaveta; Mileeva, Ekaterina; Pirkhalo, Anna; Makarova, Taiana; Vlasik, Roman; Karyagina, Elena; et al. (Frontiers in Oncology, 2023)
Introduction Tyrosine kinase inhibitor (TKI) therapy has greatly improved the prognosis of patients with chronic myeloid leukemia (CML), improving the survival expectancy of patients with chronic phase (CP) CML to that of the general population. However, despite these advances, nearly 50% of patients with CP CML experience failure to respond to frontline therapy, and most fail to respond to the subsequent second-line TKI. Treatment guidelines for patients failing second-line therapy are lacking. This study aimed to determine the efficacy of TKIs as third-line therapy in a “real-world” clinical practice setting and identify factors favorably influencing the long-term outcomes of therapy. Methods We have retrospectively analyzed the medical records of 100 patients with CP CML. Results The median age of the patients was 51 (range, 21–88) years, and 36% of the patients were men. The median duration of the third-line TKI therapy was 22 (range, 1– 147) months. Overall, the rate of achieving complete cytogenetic response (CCyR) was 35%. Among the four patient groups with different levels of responses at baseline, the best results were achieved in the groups with any CyR at the baseline of third-line therapy. Thus, СCyR was reached in all 15 and 8/ 16 (50%) patients with partial cytogenetic response (PCyR) or minimal or minor CyR (mmCyR), respectively, whereas CCyR was detected only in 12/69 (17%) patients without any CyR at baseline (p < 0.001). Univariate regression analysis revealed that the factors negatively associated with CCyR achievement in thirdline TKI therapy were the absence of any CyR on first- or second-line TKI therapy (p < 0.001), absence of CHR prior to third-line TKI (p = 0.003), and absence of any CyR prior to third-line TKI (p < 0.001). During the median observation time from treatment initiation to the last visit [56 (4–180) months], 27% of cases progressed into accelerated phase or blast phase CML, and 32% of patients died. Discussion Progression-free survival (PFS) and overall survival (OS) were significantly higher in patients with CCyR on third-line than in the group without CCyR on third-line therapy. At the last visit, third-line TKI therapy was ongoing in 18% of patients, with a median time of treatment exposure of 58 (range, 6–140) months; 83% of these patients had stable and durable CCyR, suggesting that patients without CHR at baseline and without CCyR at least by 12 months on third-line TKI should be candidates for allogeneic stem cell transplantation, third-generation TKIs, or experimental therapies.